ANALISIS KINERJA INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH âKANJURUHANâ KEPANJEN KABUPATEN MALANG DENGAN PENDEKATAN BALANCED SCORECARD - , IKA RATNA HIDAYATI; , Dr. Satibi, S.Si., M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
General Hospital Pharmacy of Kanjuruhan is one of the division which had integrated with another division settled in General Hospital of Kanjuruhan, Kepanjen, Malang Resident. Although, this General Hospital Pharmacy of Kanjuruhan havenât made any measurement of performance, so that the success length of tangible and intangible assets management in order to extend the organization vision and mission still unrecognized. Besides, measurement of performance also required to establish the hospital accreditation process. Balanced scorecard is a method to analyze the performance in General Hospital Pharmacy of Kanjuruhan. This research is purposed to analyze the performance in the General Hospital Pharmacy of Kanjuruhan by using the balanced scorecard approachment through four perspectives such as study and development, internal business process, customer, and financial. This research is a non experimental descriptive research. The information had gathered from prospective and retrospective methods. The qualitative data had acquired through questioner and intensive interview with The Head of General Hospital Pharmacy of Kanjuruhan, Kepanjen, Malang Resident. The quantitative data held through direct observation, prescription survey, and financial report. Result of the research indicate that : 1) Performance of study and development perspective: a. Human capital : incapability to innovate the work in progress, the organization custom doing well in the General Hospital Pharmacy, but the information technology operational still underrated. 2) Performance of internal business process perspective: Average dispensing time for mixture prescription is 19.34 minutes and non mixture prescription is 6,7 minutes, thought sometimes there are kinds of activities that able to issued the medication error (43), average level of medical availability is 93,7%, SOP had made as standard 5 and 6 according to hospital accreditation. 3) Performance of customer perspective: patient still unsatisfied with the given service mainly on the tangible dimension (- 0,680) and empathy dimension (-0,366), the attainable level of customer is 95% and the level of customer development is -1% each month. 4) Performance of financial perspective: Inventory Turn Over Ratio (ITOR) is 7,7 times in 2011 and 6 times in 2012, diversion between Business Plan Valuation with the actual realization is Rp. 297.868.640,- in 2011 and Rp. 787.637.726 in year 2012.